Characterization of specifically metal-binding phage clones for selective recovery of cobalt and nickel. Issue 2 (April 2020) - Matys, Sabine; Schönberger, Nora; Lederer, Franziska L.; Pollmann, Katrin
Graphical abstract: Highlights: Bacteriophages with specificity for nickel and cobalt binding were identified. Planar sol-gel ion exchange material was successfully used as target for biopanning. Combined chemical and biological phage clone elution methods were developed. Freundlich adsorption isotherms reveal characteristic binding behaviors. Abstract: Phage surface display (PSD) represents a powerful technique for isolating metal ion binding peptides. From a commercial pIII phage library, two specific peptide motifs—namely, CNAKHHPRC for nickel and CTQMLGQLC for cobalt—were identified using a specialized experimental set-up with sol-gel-coated glass fiber fabrics possessing ion exchange capacity. Employing single-clone binding experiments with immobilized Me 2+ ions on nitrilotriacetic acid (NTA) agarose beads, adsorption isotherms were determined for both the phage clones and the reference clone without a peptide insert which clearly indicate specificity of the identified phage clones for their respective target ion. The mechanisms involved in phage binding to agarose beads could be satisfactorily described using the Freundlich model. In all experiments, two fractions of phages were reproducibly identified: those chemically eluted with glycine, and a second, smaller fraction that could be eluted only by direct incubation with the host organism E. coli ER 2738. The results demonstrate that metal ion-specific phage clones can be identified and characterized in terms of their binding strength with this experimental setup. In perspective, this approach can facilitate the identification of well suited phage clones for the further development of new element specific biosorptive materials for the recovery of heavy metals from dilute aqueous solutions, e.g. industrial waste waters.